Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006744.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Alpha blockers prior to removal of a catheter for acute urinary retention in adult men

Abstract: The limited available evidence suggests that alpha blockers increase success rates of TWOC. Alpha blocker side effects are low and comparable to placebo. It is uncertain whether alpha blockers reduce the risk of recurrent urinary retention and need for prostate surgery. The cost effectiveness and recommended duration of alpha blocker treatment after successful TWOC remains unknown. There are a lack of internationally agreed outcome measures for what constitutes successful TWOC. This makes meta-analysis difficu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 21 publications
0
21
0
1
Order By: Relevance
“…The overall findings favored the use of alpha-blockers in comparison to placebo regardless of alpha-blocker used (alfuzosin: RR 1.31, 95% CI 1.10 to 1.56; tamsulosin: RR 1.86, 95% CI 1.17 to 2.97). [22] The use of alpha-blockers before and during TWOC means more patients are able to be discharged without the need of a catheter reducing the complications and discomfort associated with catheters.…”
Section: Introductionmentioning
confidence: 99%
“…The overall findings favored the use of alpha-blockers in comparison to placebo regardless of alpha-blocker used (alfuzosin: RR 1.31, 95% CI 1.10 to 1.56; tamsulosin: RR 1.86, 95% CI 1.17 to 2.97). [22] The use of alpha-blockers before and during TWOC means more patients are able to be discharged without the need of a catheter reducing the complications and discomfort associated with catheters.…”
Section: Introductionmentioning
confidence: 99%
“…Numbers were small in these categories, however, and a study that included more patients may yield different results. Some clinicians advocate for patients be given alpha blocker medications before catheter removal to improve the likelihood of successful voiding by reducing outlet resistance [42]. Further study of this tactic would be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Although some studies reported no benefit with alpha-blocker treatment after AUR, a recent meta-analysis concluded that alpha blockers increase the success rates of TWOC. [20][21][22] Djavan et al found that a residual volume of less than 1 litre after catheter removal was associated with a higher success rate for TWOC. 23 Daly et al found that patients with elevated PSA (higher than 2.9 ng/ml), large prostate size and urine volume over 1000 ml drained at catheterisation are more likely to fail a TWOC.…”
Section: Discussionmentioning
confidence: 99%